2016
DOI: 10.1016/j.egja.2016.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing surgical field during cochlear implant surgery in children: Dexmedetomidine versus Esmolol

Abstract: Background: The field of cochlear implantation has been expanding rapidly and it has been hailed as one of the greatest advances in otology. The technique of anesthesia plays a crucial role in success of cochlear implant surgery as the anesthesiologist has to produce conditions which facilitate surgery by inducing bloodless operative field. Study objective: To determine the efficacy of dexmedetomidine versus esmolol usage as an adjunct to induce controlled hypotension in children undergoing cochlear implant su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…However, this intervention had no effect on the intraoperative ESRT. TIVA using propofol and remifentanil anesthesia provides satisfactory surgical conditions as they can be titrated to the desired mean arterial blood pressure, not interfere with the ESRT testing, allows rapid emergence from anesthesia with a faster discharge from the PACU,[ 10 11 ] and less postoperative nausea and vomiting. [ 12 ] However, large doses of intraoperative remifentanil usually result in hyperalgesia and there is more need of postoperative opioid rescue[ 13 ] Opioid analgesics compound the problem of PONV, cause excessive sedation, and delay discharge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this intervention had no effect on the intraoperative ESRT. TIVA using propofol and remifentanil anesthesia provides satisfactory surgical conditions as they can be titrated to the desired mean arterial blood pressure, not interfere with the ESRT testing, allows rapid emergence from anesthesia with a faster discharge from the PACU,[ 10 11 ] and less postoperative nausea and vomiting. [ 12 ] However, large doses of intraoperative remifentanil usually result in hyperalgesia and there is more need of postoperative opioid rescue[ 13 ] Opioid analgesics compound the problem of PONV, cause excessive sedation, and delay discharge.…”
Section: Discussionmentioning
confidence: 99%
“…The mean and standard deviation of the postoperative tramadol consumption from a previous study were respectively 18.25 mg and 11.57 mg.[ 10 ] A minimum sample size should be 30 patients per group was needed to detect a 8.5 mg reduction in tramadol consumption, with a significance level 5% and a power of 90%. A total sample size of, 70 patients were included to allow for a dropout rate of 15%.…”
Section: Methodsmentioning
confidence: 99%
“…Amin et al, concluded that, both dexmedetomidine and esmolol are safe and effective in inducing controlled hypotension which decrease the surgical area bleeding score and provide ideal surgical condition in children undergoing cochlear implant surgery under general anesthesia [11]. Shams et al reported that, both dexmedetomidine and esmolol were used in patients undergoing FESS and it was found to be safe agents for inducing controlled hypotension and effective in providing better surgical field.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Amin et al concluded that, dexmedetomidine decrease postoperative opioid consumption in children undergoing cochlear implant surgery when compared to patients received esmolol [11].…”
Section: Discussionmentioning
confidence: 99%
“…Amin and El-Mawy [35] studied optimizing surgical field during cochlear implant surgery in children by dexmedetomidine versus esmolol and found that the time to first analgesic request was statistically significant longer in dexmedetomidine group.…”
Section: Gao Et Al [19]mentioning
confidence: 99%